Usability of bank capital buffers - Abad, José M.,Garcia Pascual, Antonio (International Monetary Fund, 2022)
Following the COVID shock, supervisors encouraged banks to use capital buffers to support the recovery. However, banks have been reluctant to do so. Provided the market expects a bank to rebuild its buffers, any draw-down will open up a capital shortfall that will weigh on its share price. Therefore, a bank will only decide to use its buffers if the value creation from a larger loan book offsets the costs associated with a capital shortfall. Using market expectations, we calibrate a framework for assessing the usability of buffers. Our results suggest that the cases in which the use of buffers make economic sense are rare in practice
10.5089/9781616358938.001
Keywords: Graue Literatur; Capital Buffers; Basel III; Capital Regulation; Macropru; Financial Institutions and Services; Financial Institutions; Banks; Depository Institutions; Micro Finance Institutions; Mortgages; Diseases: Contagious; Financial Institutions and Services: General; Economics: General; Banks and Banking; Industries: Financial Services; Finance: General; Financial Institutions and Services: Government Policy and Regulation; International Lending and Debt Problems; Financial Markets and the Macroeconomy; Health Behavior; Economic & financial crises & disasters; Economics of specific sectors; Financial services law & regulation; Finance; Banking; Infectious & contagious diseases; Countercyclical capital buffers; Financial regulation and supervision; Correspondent banking; Financial services; Macroeconomics; Market capitalization; Financial markets; COVID-19; Health; Currency crises; Informal sector; Economics; Asset requirements; Correspondent banks; Loans; Financial services industry; Communicable diseases